Noble Metal-Loaded WO3-Based Gases—The Gold Anomaly - Anna Staerz; Udo Weimar; Nicolae Barsan (Proceedings)
Tungsten oxide is one of the most commonly used materials for metal oxide-based gas sensors. In order to tune the sensing behavior, small clusters of noble metals are often added to the surface of WO3. Previously, it has been found that in the case of oxidized metal clusters, e.g., Rh and Pt additives, the Fermi-level pinning mechanism dominates. Unlike other noble metal surface clusters, gold seems to remain metallic under sensor operation. As a result, the behavior of WO3-based sensors was found to be significantly enhanced for all reducing gases and decreased for NO2.